2006
DOI: 10.1002/prot.21116
|View full text |Cite
|
Sign up to set email alerts
|

Conformational flexibility of RecA protein filament: Transitions between compressed and stretched states

Abstract: RecA protein is a central enzyme in homologous DNA recombination, repair and other forms of DNA metabolism in bacteria. It functions as a flexible helix-shaped filament bound on stretched single-stranded or double-stranded DNA in the presence of ATP. In this work, we present an atomic level model for conformational transitions of the RecA filament. The model describes small movements of the RecA N-terminal domain due to coordinated rotation of main chain dihedral angles of two amino acid residues (Psi/Lys23 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The polymerization motif of the E.coli RecA protein resides between its small NTD (amino acid residues 1–22) and the core ATPase domain (amino acid residues 36–353) (29). A recent structural study reported that changes in the dihedral angles of two amino acid (Lys23 and Gly24) residing in the polymerization motif were responsible for rotation of the RecA filament between compressed and stretched conformations (32). We noticed that Arg34 formed a salt bridge with Glu19 in a compressed RecA helical filament (74 Å helical pitch; 33), and this salt bridge fell apart in a relaxed RecA helical filament (83 Å helical pitch; 29) (Figure 10).…”
Section: Discussionmentioning
confidence: 99%
“…The polymerization motif of the E.coli RecA protein resides between its small NTD (amino acid residues 1–22) and the core ATPase domain (amino acid residues 36–353) (29). A recent structural study reported that changes in the dihedral angles of two amino acid (Lys23 and Gly24) residing in the polymerization motif were responsible for rotation of the RecA filament between compressed and stretched conformations (32). We noticed that Arg34 formed a salt bridge with Glu19 in a compressed RecA helical filament (74 Å helical pitch; 33), and this salt bridge fell apart in a relaxed RecA helical filament (83 Å helical pitch; 29) (Figure 10).…”
Section: Discussionmentioning
confidence: 99%
“…Filaments of RecA protein from D. radiodurance can assume 'open' and 'closed' conformation, similar to those seen in RecA proteins from E. coli and P. aeruginosa [7][8][9][10]. Large N-terminal domain of RecA Dr does not seem to hinder this motion, which in case of E. coli RecA filament can be explained by a coordinated rotation of two neighbouring amino acids forming a single hinge in the N-terminal domain of the protein [22]. The data also show that just like ssDNA, dsDNA binding results in stretching of the enzyme in the active form, with the pitch increasing to the value conservative for a number of RecA proteins and their functional analogs.…”
Section: Resultsmentioning
confidence: 61%
“…One could expect that any significant change in the number of monomers per turn during conformational transition would require extensive unwinding or disassembly of the filament. Although in the earlier works the transition between active and inactive filament of E. coli RecA has been reported to involve change in the filament mass per turn [7], the later models suggest the number of monomers per turn to be very similar in different conformations of the filaments [9,21,22].…”
Section: Resultsmentioning
confidence: 94%
“…This change in the filament geometry is required to accommodate the stretched form of the DNA [7], which seems to be an essential intermediate in the process of homologous pairing and strand exchange. Similar largescale conformational flexibility of the filament can be observed under conditions of high ionic strength in the absence of DNA, thus being inherent property of the enzyme, and is accomplished largely by Nterminal domain motion [8]. There are indications, however, that the transition between the two conformational states may be more complex and involve the motion of the C-terminal domain and the unstructured regions of RecA monomer, particularly the unstructured C-terminal tail [8;9].…”
Section: Introductionmentioning
confidence: 96%